1993
DOI: 10.1007/bf00201404
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic and electric fields induced by superparamagnetic magnetite in honeybees

Abstract: Abstract.Hairs on the abdomen of honeybees contain dendrites and a rod and ring structure composed of black particles, presumed to be superparamagnetic (SPM) magnetite. The rod and ring were divided into compartments and each compartment approximated by a dipole. The magnetic fields were calculated at a point P at various locations for a change of the external geomagnetic field from zero to 0.5 G in 0.1 s. The magnetite amplifies the external field at the rod/ring-dendrite interface. The induced electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The relaxation time is then very short as compared to the neurological response times in honeybees and reinforces the superparamagnetic character. It was suggested that in honeybees, superparamagnetic magnetite is involved in gradient detection by locally amplifying changes in the geomagnetic field (Schiff and Canal, 1993). Similar to other social insects such as bees, ants could take advantage of the almost instantaneous response of superparamagnetic particles to a magnetic intensity gradient involved in a map sense orientation (Schiff, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The relaxation time is then very short as compared to the neurological response times in honeybees and reinforces the superparamagnetic character. It was suggested that in honeybees, superparamagnetic magnetite is involved in gradient detection by locally amplifying changes in the geomagnetic field (Schiff and Canal, 1993). Similar to other social insects such as bees, ants could take advantage of the almost instantaneous response of superparamagnetic particles to a magnetic intensity gradient involved in a map sense orientation (Schiff, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Schiff & Canal (1993) developed a model based on agglomerated SPM magnetite in the hair of bee abdomens. These particles were considered to be arranged in a rod and a ring, which can be aligned by the geomagnetic field.…”
Section: Ferromagnetic Hypothesismentioning
confidence: 99%
“…Iron-containing trophocytes were found within the fat body of this adult honeybee (Kuterbach & Walcott 1986), identified as superparamagnetic (SPM) magnetite particles (Hsu & Li 1994), although this result was not reproduced. Electron-dense material found in the hairs of honeybee abdomens or near the cutex was proposed as single domain or SPM magnetite (Schiff 1991) and a hypothesis was developed for associative learning of visual and magnetic stimuli (Schiff & Canal 1993). The presence of iron particles were also observed by optical and electron microscopy in the trophocytes of adult Scaptotrigona postica, a stingless honeybee (Cunha et al 1987).…”
Section: Introductionmentioning
confidence: 99%